2015
DOI: 10.1371/journal.pone.0145418
|View full text |Cite
|
Sign up to set email alerts
|

S100A1 as a Potential Diagnostic Biomarker for Assessing Cardiotoxicity and Implications for the Chemotherapy of Certain Cancers

Abstract: This study examined the value of blood marker S100A1 in detecting cardiotoxicity induced by chemotherapy agents; trastuzumab and lapatinib, in normal rat heart. The rats were divided into three groups: control (n = 8, no treatment), T (n = 8, one time ip treatment with 10 mg/kg trastuzumab) and L (n = 8, oral treatment with 100 mg/kg/day lapatinib for 7 days). The activities of oxidative stress parameters Malondialdehyde (MDA), Superoxide dismutase (SOD), Catalase (CAT) and Glutathione (GSH) were measured from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The crucial role of S100A1 for cardiac performance and contractility was reported (20,21). In our study, reduced release of S100A1 from injured cardiomyocytes to serum after CIS exposure was demonstrated, which was concordant with our previous study (22). Lapatinib and Trastuzumab decreased S100A1 expression in a ratio of %75.…”
Section: Discussionsupporting
confidence: 93%
“…The crucial role of S100A1 for cardiac performance and contractility was reported (20,21). In our study, reduced release of S100A1 from injured cardiomyocytes to serum after CIS exposure was demonstrated, which was concordant with our previous study (22). Lapatinib and Trastuzumab decreased S100A1 expression in a ratio of %75.…”
Section: Discussionsupporting
confidence: 93%
“…Various heart diseases are related to S100 proteins which are considered as new markers for cardiac toxicity [13]. S100A1 protein improves cardiac contractility and its expression is reduced following cardiac damage [14]. Human cardiomyopathy exhibited down-regulation of S100A1 expression that decreased the performance of myocardial contraction as documented by Remppis et al [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that S100A1 is most abundant in cardiomyocytes [17] and finds in the extracellular compartment after heart ischemia [18]. In our previous study, we have shown the disruption of S100 A1 after exposure of lapatinib or trastuzumab therapy [19]. Beside of the Troponin I and MDA levels, S100 A1 level did not give any significant changing value.…”
Section: Discussionmentioning
confidence: 62%